Challenges and concerns of patients with congenital bleeding disorders affected by coronavirus disease 2019. Issue 3 (April 2021) - Dorgalaleh, Akbar; Tabibian, Shadi; Baghaipour, Mohammad Reza; Dabbagh, Ali; Bahoush, Gholamreza; Jazebi, Mohammad; Bahraini, Mehran; Fazeli, Alieh; Yousefi, Forough
Abstract : N/A: Coronavirus disease 2019 (COVID-19) is a new medical challenge for all individuals, especially for those with underlying disorders, such as congenital bleeding disorders (CBDs). Therefore, the pandemic might significantly change the behaviour of patients with CBDs and results in some challenges. In the present study, we assessed the main challenges of COVID-19 infection to patients with CBDs. Data were collected from medical files and interviews of patients with CBDs who had COVID-19 infection. Follow-ups were performed on patients who had active severe acute respiratory syndrome coronavirus 2 infection between April and October 2020. All patients were interviewed by an expert in order to collect the pertinent data. Some questions were about patients' preventive behaviors and feelings prior to infection, and some were about the consequences of infection on patients' replacement therapy and bleeding management. Among 25 patients, infection and death of loved ones ( n : 7, 28%), and their own ( n : 5, 20%) or family members' ( n : 1, 4%) infection, and the resulting economic burden ( n : 2, 8%) were main concerns. Six patients experienced depression during the pandemic. The pandemic caused all severely affected patients but one ( n : 11, 92%) to abandon replacement therapy. However, two received on-demand therapy after exacerbation of their bleeding. Only one (25%) of four patients on prophylaxis received in-home therapy, whereas the others (75%) abandoned prophylaxis. It seems that COVID-19 infection has great consequences on the lives of patients with CBDs, causing some to take dangerous actions, such as abandonment of their treatment. Healthcare systems, and healthcare providers, should have an appropriate strategy for management of patients with CBDs that prevents infection and provides timely replacement therapy.